IMPLEMENTATION OF COMMUNITY DEVELOPMENT: NASYIATUL AISYIYAH'S ROLE IN CREATING WOMEN-FRIENDLY AND CHILD-CARING VILLAGES - Fatmawati Fatmawati; Rusliadi Rusliadi; Subaedah Subaedah (Natapraja, 2025)
Women and children’s issues in Indonesia include high rates of domestic violence and gender inequality that impact access to education, health and economic opportunities. This research aims to analyse the implementation of community development related to the impact of the role of the Central Leadership of Nasyiatul Aisyiyah’s, which is one of Muhammaidiyah’s autonomous organisations, in creating women-friendly and child-caring villages in Indonesia. This study utilized Muhtadi’s Community Development theory with indicators of participation, gender equality and justice, democracy, transparency and accountability, and sustainability. This research uses qualitative research methods with data collection techniques based on observation, interviews and document studies. Data were analyzed with several tools, including Biblioshiny and Nvivo 12 Pro to obtain in-depth analysis. This study shows that Nasyiatul Aisyiah collaborates with the Ministry of Women’s Empowerment and Child Protection, Village Governments spread across 4 Provinces, 8 Districts, 16 Districts and 16 Villages in Indonesia. Overall, the role of Nasyiatul Aisyiah in running the Women-Friendly Village and Child Care programme has a positive effect on the legal protection of women and children from violence. It also provides full access to the percentage of women included in the village government system. However, in reality, not all villages in Indonesia provide a clear legal umbrella through village regulations to follow up on the Women-Friendly and Child-Caring Village programme. Therefore, the central government needs to promote Village Regulations and engage non-governmental institutions to sustain the Women-Friendly and Child-Caring Village programme.